Penghalusan Kata; Linguistik Modern dan Penerapannya dalam Pendidikan Bahasa Arab - Muhammad Zakki Masykur (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
Euphemism is A word or figure of speech that makes something look prettier than it is. A euphemism is a generally innocuous word or expression used in place of one that may be found offensive or suggest something unpleasant. Some euphemisms are intended to amuse; while others use bland, inoffensive, and often misleading terms for things the user wishes to dissimulate or downplay. Euphemisms are used for dissimulation, to refer totaboo topics in a polite way, and to mask profanity. Euphemisms may be used to avoid words considered rude, while still conveying their meaning; words may be replaced by similar-sounding words, gentler words, or placeholders. Some euphemisms have become accepted in certain societies for uncomfortable information; for example, in many English speaking countries, a doctor is likely to say ‘the patient passed away’ rather than the patient died. A second example relating uncomfortable information and concealing some degree of truth would be ‘we put the dog to sleep’ rather than we killed the dog. Euphemisms can be used to downplay or conceal unpalatable facts, such as collateral damage for civilian casualties in a military context, or redacted for censored